2018
DOI: 10.1177/1055665618771427
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Soft Tissue Nasal Changes After Nasoalveolar Molding and Primary Cheilorhinoplasty in Infants With Unilateral Cleft Lip and Palate

Abstract: Three-dimensional analysis of UCL±P patients demonstrated significant improvements in nasal projection, columella length, nasal symmetry, and nasal width. Compared to noncleft controls, nasal form was generally corrected, with overcorrection of nasal tip projection, columella angle, and outer nasal widths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 31 publications
(32 reference statements)
2
43
0
5
Order By: Relevance
“…However, only a few studies have used (3D) stereophotogrammetry for evaluation of facial growth and treatment outcome in infants with OFCs until 12 months of age. Two studies used linear and angular measurements for evaluation of facial morphology before and after primary lip closure (Alazzawi et al, 2017; Morioka et al, 2018), and one study also made a comparison with the facial morphology of a control sample (Mancini et al, 2018). Furthermore, one study used superimposition of individual 3D images for evaluation of facial morphology before and after nasoalveolar molding and primary cheilorhinoplasty (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have used (3D) stereophotogrammetry for evaluation of facial growth and treatment outcome in infants with OFCs until 12 months of age. Two studies used linear and angular measurements for evaluation of facial morphology before and after primary lip closure (Alazzawi et al, 2017; Morioka et al, 2018), and one study also made a comparison with the facial morphology of a control sample (Mancini et al, 2018). Furthermore, one study used superimposition of individual 3D images for evaluation of facial morphology before and after nasoalveolar molding and primary cheilorhinoplasty (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This observational time interval is not a long-term result, but overall we and others achieved good short-term results. 15 Mancini et al reported improved nasal projection, nasal width and nasal symmetry, and columella length in a 3D analysis of 20 consecutively treated cases with UCLP. Barillas et al reported that the good results were maintained at least until the age of 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed for the opportunity to enlarge and rotate the digital models in all the 3 planes (Bootvong et al, 2010) including the vertical plane—as there is a tendency in the cleft deformity that the alveolar ridges grow or move in vertical direction when there is no supporting vector present on the vertical direction. Furthermore, 3-D anthropometric assessment have proven to superior in the overall of the naso-labial and alveolar outcome assessment post-NAM in patients with CLP when compared to 2-D assessments (Chou et al, 2017; Singh et al, 2005; Singh et al, 2007; Mancini et al, 2019). While our 3-D assessment has been primarily focused on the cast based changes, given that the findings of our study are in line with the abovementioned studies with regard to nostril width (similar decrease), height (comparable increase), and columellar axis change (equivalent increase), a more detailed 3-D assessment of the facial changes including those from the profile view would be interesting to assess.…”
Section: Discussionmentioning
confidence: 99%